Cabin1 involves in renal tubular epithelial cells mitochondrial dysfunction through SIRT1/p53 pathway. (3rd March 2020) - Wen, Yueqiang; Chen, Jieru; Liu, Lingling; Guo, Guanhua; Zeng, Yinsi; Zhang, Yujing; Zeng, Zhili; Wang, Zebin; Peng, Xuan; Liang, Jianbo
Abstract: Background: Angiotensin II (AngII) induced Calcineurin binding protein 1 (Cabin1) protein expression significantly increased during Renal tubular epithelial cells (RTEC) injury. However, the detailed function of Cabin1 protein in RTEC was not characterized well. In this study, we aimed to explore the downstream target of Cabin1 in vitro model. Methods: Rat kidney epithelial cells were cultured and stimulated with AngII. Electron microscopy was performed to observe mitochondrial morphology change. Immunofluorescence staining was detected to observe the distribution of cytoskeleton and Cabin1. Mitochondrial morphology change and protein expression were detected by electrical microscopy and western blot. Results: AngII induced the disruption of cytoskeleton at 24 and 48 h. Western blot analysis showed AngII significantly induced the overexpression of Cabin1. AngII induced a great deal of small, long and irregular mitochondria in RTEC, aspect ratio which reflects the length-to-width ratio of mitochondria remarkably increased at 12 and 24 h. Knocking down Cabin1 aggravated mitochondrial morphological abnormality in AngII treated RTEC. In comparison with control, Cabin1, p53 and cyto C level were significantly increased in AngII treated cells, while SIRT1 level was obviously decreased. Knocked down Cabin1 plus AngII stimulated, SIRT1 was further decreased, while p53 and cyto C were significantly increased. Conclusions: Cabin1 involves in RTEC mitochondrial dysfunction through SIRT1/p53 pathway. Cabin1 may be used as a new marker for the mechanisms of RTEC injury.